Biomechanical analysis using infrared thermography of a traditional metal plate versus a carbon fibre/epoxy plate for Vancouver B1 femur fractures. (January 2014) - Siddiqui, Faisal S; Shah, Suraj; Nicayenzi, Bruce; Schemitsch, Emil H; Zdero, Radovan; Bougherara, Habiba
Traditional high-stiffness metal plates for Vancouver B1 femur shaft fractures below the tip of a hip implant can cause stress shielding, bone resorption, and implant loosening. This is the first study to compare the biomechanics of a traditional metal plate versus a low-stiffness carbon fibre/epoxy composite plate for this injury. A total hip replacement was implanted in two previously validated intact artificial femurs. Femurs were fitted with either a metal or composite plate and had a 5 mm fracture gap created to simulate a Vancouver B1 shaft fracture. Femurs were cyclically loaded using 5 Hz at 7° of adduction with an average axial load of 800 N (range = 400–1200 N). Overall mechanical stiffnesses and femur and plate thermographic stresses were obtained. Femur/metal plate stiffness (698 N/mm) was only 12% higher than femur/composite plate stiffness (625 N/mm). The femur with the composite plate had 22.7% higher combined average stress compared to the femur with the metal plate, having specific differences of 29.5% (anterior view), 33.9% (posterior view), 1.0% (medial view), and 26.4% (lateral view). The composite plate itself had an average 21.1% reduction in stress compared to the metal plate. The composite plate reduced stress shielding, yet provided adequate stiffness.